2022
DOI: 10.1101/2022.10.28.514057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Augmenting TCR signal strength and ICOS costimulation results in metabolically fit and therapeutically potent human CAR Th17 cell therapy

Abstract: Adoptive cell transfer (ACT) therapy with IL-17 producing human T cells elicits potent antitumor activity in preclinical models. However, further refinement of this novel approach is needed to position it for clinical application. While activation signal strength differentially regulates IL-17 production by human CD4+ T cells, the degree to which TCR and co-stimulation signal strength impacts antitumor Th17 cell immunity remains poorly understood. We discovered that decreasing TCR/co-stimulation signal strengt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is possible that PIP5K1α plays additional roles in driving IL-17 production by memory T H 17 cells through supporting TCR/CD28 signaling in addition to enhancing IL-17A protein production, but this remains to be tested. In this context, it is worth highlighting that CD28 inhibits T H 17 cell generation in a dose-dependent manner when using agonistic anti-CD28 in vitro, and this inhibition can be mitigated by reducing the concentration of anti-CD3 ( 14 , 39 ). In other words, cumulative signals from the TCR and CD28 determine T H 17 cell output, much like what has been described for T H 1 and T H 2 cells ( 14 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that PIP5K1α plays additional roles in driving IL-17 production by memory T H 17 cells through supporting TCR/CD28 signaling in addition to enhancing IL-17A protein production, but this remains to be tested. In this context, it is worth highlighting that CD28 inhibits T H 17 cell generation in a dose-dependent manner when using agonistic anti-CD28 in vitro, and this inhibition can be mitigated by reducing the concentration of anti-CD3 ( 14 , 39 ). In other words, cumulative signals from the TCR and CD28 determine T H 17 cell output, much like what has been described for T H 1 and T H 2 cells ( 14 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ICOS signaling is a strong costimulatory signal for T cells and is required for the proper functionality of activated T cells. 42 Further, ICOS stimulation has been shown to augment T cell 43 and NK functionality. 44,45 To test whether concomitant activation of ICOS signaling in NK-92/CD3/CD8 cells expressing a TCR could enhance TCR-mediated cytotoxicity, we first generated a T2-derived cell line constitutively expressing ICOSL (Figure 4A).…”
Section: Design and Construction Of A L1-cam Ssdcarmentioning
confidence: 99%